2016
DOI: 10.7554/elife.17440
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin-proteasome system regulates focal adhesions at the leading edge of migrating cells

Abstract: Cell migration requires the cyclical assembly and disassembly of focal adhesions. Adhesion induces phosphorylation of focal adhesion proteins, including Cas (Crk-associated substrate/p130Cas/BCAR1). However, Cas phosphorylation stimulates adhesion turnover. This raises the question of how adhesion assembly occurs against opposition from phospho-Cas. Here we show that suppressor of cytokine signaling 6 (SOCS6) and Cullin 5, two components of the CRL5SOCS6 ubiquitin ligase, inhibit Cas-dependent focal adhesion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 89 publications
2
40
0
Order By: Relevance
“…However, these cells also saw an increase in long fibrillar adhesions (Fig.S3D). These findings suggest that NEDD9 is also required for the disassembly of fibrillar adhesions similar to vinculin (43), which regulates the recruitment and release of focal adhesion proteins in a force-dependent manner (44). The role of NEDD9/HEF1 as a sensor of altered adhesion states has been previously reported (45).…”
Section: Discussionmentioning
confidence: 99%
“…However, these cells also saw an increase in long fibrillar adhesions (Fig.S3D). These findings suggest that NEDD9 is also required for the disassembly of fibrillar adhesions similar to vinculin (43), which regulates the recruitment and release of focal adhesion proteins in a force-dependent manner (44). The role of NEDD9/HEF1 as a sensor of altered adhesion states has been previously reported (45).…”
Section: Discussionmentioning
confidence: 99%
“…The LED array for illuminating cells for biochemistry was made according to the methods as described4546. Briefly, 6 LED bulbs and the BuckPuck LED driver were connected to an Arduino Uno microcontroller.…”
Section: Methodsmentioning
confidence: 99%
“…FAK, ERK, paxillin, the myosin light chain kinase, and p130Cas, have all been shown to be critical for focal adhesion disassembly because the absence of these proteins leads to more stable structures . More recent work, focused specifically on p130Cas, demonstrated that adhesion‐mediated tyrosine phosphorylation of this protein recruits an E3 ubiquitin ligase leading to p130cas degradation . Since the absence of p130Cas promotes focal adhesion stability, its selective degradation in some adhesions but not others provides a potential mechanism for the differential behavior of neighboring adhesions at the front of migrating cells.…”
Section: Identifying the Pathways To Focal Adhesion Disassemblymentioning
confidence: 99%
“…Since the absence of p130Cas promotes focal adhesion stability, its selective degradation in some adhesions but not others provides a potential mechanism for the differential behavior of neighboring adhesions at the front of migrating cells. In this scenario, disassembly is favored for those adhesions containing p130Cas, whereas p130Cas destruction promotes adhesion survival and growth . The mechanism by which adhesions are disassembled downstream from p130Cas has not been established.…”
Section: Identifying the Pathways To Focal Adhesion Disassemblymentioning
confidence: 99%